Research of the chemical composition of Artemisia tschernieviana Bess. by gas chromatography method with mass detection - O. I. Panasenko; V. I. Mozul; O. M. Denysenko; I. I. Aksonova; V. V. Holovkin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work was to study chromato-mass spectroscopic of Artemisia tschernieviana Bess. grass and to establish possible prospects for the use of this plant in medical practice.